PENGARUH LAYANAN PRAMUWISATA LOKAL TERHADAP LOYALITAS WISATAWAN DI DESA WISATA BONJERUK LOMBOK TENGAH - Zainul Latif; I.A.Y.S.D Utami Pidada; Supardi, Supardi (Juremi: Jurnal Riset Ekonomi, 2024)
The role of a tour guide in the tourism sector is the main component that influences the success of a travel service. Tour guides are known as professional people who have extensive knowledge about a tourist spot, are able to provide in-depth information to tourists, and have skills in organizing and arranging tourist trips to ensure a satisfying experience for visitors. This research aims to determine the influence of the quality of local tour guide services on tourist loyalty in coming back to the Bonjeruk tourist village. This research method is descriptive quantitative with data collection techniques, namely questionnaires, documentation and literature study. The sampling technique used purposive sampling by distributing questionnaires to 100 respondents. This research uses four excellent service quality variables as independent variables, including friendliness, comfort, speed and accuracy in service and the dependent variable, namely tourist loyalty. The research results obtained showed that there was a simultaneous influence of excellent service quality on tourist loyalty by 53.7% and the remaining 46.3% was influenced by variables not examined in this research, and there was a relationship between excellent service quality and tourist loyalty